Restoring Lumino-Kinetic art - Olivier Steib (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This paper sum up the different steps and decisions taken during the restoration of two Mobiles Lumineux made by Nino Calos (1926-1990) and conserved in the Museum of Modern Art of Paris. This article highlights the problematic of the obsolescence of the lighting systems, and how to resolve it.